A Multiplexed Microfluidic Platform for Bone Marker Measurement: A Proof-of-Concept - Khashayar, Patricia (Micromachines (Basel), 2017)
In this work, we report a microfluidic platform that can be easily translated into a biomarker diagnostic. This platform integrates microfluidic technology with electrochemical sensing and embodies a reaction/detection chamber to measure serum levels of different biomarkers. Microfabricated Au electrodes encased in a microfluidic chamber are functionalized to immobilize the antibodies, which can selectively capture the corresponding antigen. An oxidative peak is obtained using the chronoamperometry technique at room temperature. The magnitude of the response current varies linearly with the logarithmic concentration of the relative biomarker and, thus, is used to quantify the concentration of the relative biomarker in serum samples. We demonstrated the implementation, feasibility and specificity of this platform (Osteokit) in assaying serum levels of bone turnover markers (BTMs) using osteocalcin (limits of detection (LOD) = 1.94 ng/mL) and collagen type 1 cross-linked C-telopeptide (CTX) (LOD = 1.39 pg/mL). To our knowledge, this is the first such device fabricated to measure BTMs. Our results also showed that the sensitivity of Osteokit is comparable with the current states of art, electrochemiluminescence (ECLIA).